2014
DOI: 10.1590/s1980-57642014dn84000002
|View full text |Cite
|
Sign up to set email alerts
|

Building capacity for dementia care in Latin America and the Caribbean

Abstract: Latin America and the Caribbean (LAC) have limited facilities and professionals trained to diagnose, treat, and support people with dementia and other forms of cognitive impairment. The situation for people with dementia is poor, and worsening as the proportion of elderly in the general population is rapidly expanding. We reviewed existing initiatives and provided examples of actions taken to build capacity and improve the effectiveness of individuals, organizations, and national systems that provide treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Previous studies in Latin America and the Caribbean (LAC) have indicated that the care needs of PWD are higher than those of older adults requiring care due to other medical conditions . Nevertheless, to the best of our knowledge, no published study has addressed unmet needs in PWD in LAC . Previous epidemiological studies in LAC reported a 7.1% prevalence of dementia among older adults, with high variability between countries, ranging from 2% in Brazil to 13% in Venezuela .…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies in Latin America and the Caribbean (LAC) have indicated that the care needs of PWD are higher than those of older adults requiring care due to other medical conditions . Nevertheless, to the best of our knowledge, no published study has addressed unmet needs in PWD in LAC . Previous epidemiological studies in LAC reported a 7.1% prevalence of dementia among older adults, with high variability between countries, ranging from 2% in Brazil to 13% in Venezuela .…”
Section: Discussionmentioning
confidence: 96%
“…Unlike many HIC (e.g., United Kingdom, France, Norway, United States, and South Korea) where governments have developed specific dementia plans or strategies, most LAC have minimal mental health facilities with no specific policies or budgets for mental health. 15 Currently available treatments, research opportunities, and clinical assessment of dementia appears to depend on a country's political stability and economic capacity 16 , 30 32 (appendix e-1, S6, links.lww.com/WNL/A97 ).…”
Section: Currently Available Treatmentsmentioning
confidence: 99%
“…Stigmatization and elder abuse risk significantly increase when Alzheimer’s disease is poorly understood (Prorok, Horgon, & Seitz, 2013) hence, informational and accessible resources are critical (Gurayah, 2015). Health-care professionals and support organizations are vital in providing guidance and information about challenges and common symptoms that aid in caregiver coping (Gonzalez et al., 2015; Mintzer, Miriski, & Hoernig, 2000). Male caregivers, however, preferred limiting their knowledge on disease progression, which controlled their anxiety and enhanced their perceived coping ability (Pretorius et al., 2009).…”
Section: Introductionmentioning
confidence: 99%